IDENTIFIKASI HUKUM ADAT YANG MASIH BERLAKU DALAM PENYELESAIAN PERSOALAN SOSIAL DI DESA KAWO KABUPATEN LOMBOK TENGAH (Institut Pemerintahan Dalam Negeri, 2020)
Based on some facts that occur in indigenous peoples, it should be between customary law and national law must support each other in order to achieve civil society. The implementation of indigenous law and its implementation in the village community is important and central to be able to keep pace with the pace of globalization that is fraught with challenges and competition, restore the image of the community, as a norm that ontrol and stem all actions that violate the provisions in society. Keywords: customary law, social issues